Highlights from the Keynotes of Artificial Intelligence Conference, London 2019 - Lorica, Ben (O'Reilly Media, Inc., 2020)
This curated collection of keynote highlights from the O'Reilly Artificial Intelligence Conference in London '19 is full of useful insights and helpful guidance. For more content from this event, be sure to check out the full conference video compilation .